2013
DOI: 10.1589/jpts.25.1339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Support on Parenting Stress of Korean Mothers of Children with Cerebral Palsy

Abstract: [Purpose] This study investigated the effect of perceived social support on the parenting stress of mothers who have children with cerebral palsy (CP). [Methods] This study was conducted using surveys, literature review, and interviews. Survey data were collected from 181 mothers of children (under 18 years of age) with CP. [Results] Level of disability, mother's health status and social support were significant predictors of the parenting stress of mothers. [Conclusion] We have to comprehend and share the psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
(12 reference statements)
0
19
1
1
Order By: Relevance
“…The impairments of CP children caused various difficulties for both the children and their primary caregivers (Elllis and Hirsch ). As the caregivers of children with CP had to overcome the difficulties and complications arising from their children's impairments, they were unable to provide for their own social needs; therefore, they had lower satisfaction with life (Ones et al , Jeong et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The impairments of CP children caused various difficulties for both the children and their primary caregivers (Elllis and Hirsch ). As the caregivers of children with CP had to overcome the difficulties and complications arising from their children's impairments, they were unable to provide for their own social needs; therefore, they had lower satisfaction with life (Ones et al , Jeong et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies of leisure activities, which may improve caregivers' QoL, must be conducted. In the future, research should include a control group who have children without CP and perform a prospective study that reflects the effect of motor function improvements of children with CP to caregivers' QoL and other such emotional distress [26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies that compared the infant temperaments of normal children with those of premature children, the results of studies that compared the infant temperaments of normal newborn babies with those of high risk newborn babies 10 ) , and the results of studies that compared normal weight birth infants with low birth weight infants show that higher risk infants and lower birth weight infants have pickier infant temperaments 2 ) . Other studies have shown significant correlations between infant temperaments and a mother’s parenting stress, confidence in infant care, depression, and self-worth 11 , 12 ) .…”
Section: Discussionmentioning
confidence: 93%